Endoplasmic reticulum stress impairment in the spinal dorsal horn of a neuropathic pain model - Zhang, Enji (Sci Rep, 2015)
Endoplasmic reticulum (ER) stress has been implicated in neurodegenerative diseases, but its role in neuropathic pain remains unclear. In this study, we examined the ER stress and the unfolded protein response (UPR) activation in a L5 spinal nerve ligation (SNL)-induced rat neuropathic pain model. SNL-induced neuropathic pain was assessed behaviorally using the CatWalk system, and histologically with microglial activation in the dorsal spinal horn. L5 SNL induced BIP upregulation in the neuron of superficial laminae of dorsal spinal horn. It also increased the level of ATF6 and intracellular localization into the nuclei in the neurons. Moreover, spliced XBP1 was also markedly elevated in the ipsilateral spinal dorsal horn. The PERK-elF2 pathway was activated in astrocytes of the spinal dorsal horn in the SNL model. In addition, electron microscopy revealed the presence of swollen cisternae in the dorsal spinal cord after SNL. Additionally, inhibition of the ATF6 pathway by intrathecal treatment with ATF6 siRNA reduced pain behaviors and BIP expression in the dorsal horn. The results suggest that ER stress might be involved in the induction and maintenance of neuropathic pain. Furthermore, a disturbance in UPR signaling may render the spinal neurons vulnerable to peripheral nerve injury or neuropathic pain stimuli.